Promoting Active Citizenship : Markets and Choice in Scandinavian Welfare - Sivesind, Karl Henrik; Saglie, Jo (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is open access under a CC BY 4.0 license. This book analyses the considerable variation in the shares of private provision for core services in education, health and social services, in the Scandinavian countries. The chapters compare countries, service areas, and the for-profit, non-profit and public sectors. Each focuses on different levels of change: the mix of welfare providers, national laws and regulations, governance in municipalities, nursing homes and schools, and finally, the consequences experienced by the users of the services. The authors ask which combinations of governance structures, service sector providers, and user choice give the best results for active citizenship. Promoting Active Citizenship will be of interest to students and scholars across a range of disciplines, including Public Administration and Management, Non-Profit Management, Social Policy, Innovation in Public Service, Social Care and Education and School Research.
Keywords: Social sciences.; Social structure.; Social inequality.; Industrial sociology.; Social policy.; elektronické knihy; electronic books